2016
DOI: 10.1007/s00101-016-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Briefing verbessert das Management einer schwierigen Maskenbeatmung beim Säugling

Abstract: Briefings prior to anaesthesia induction in paediatric anaesthesia should include management of unanticipated problems. In a simulation setting, a briefing on treatment steps for an unexpected difficult airway improves management of an upper airway obstruction. Explicit communication of intended actions by the anaesthesiologist may foster speaking up by team members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…The significantly more frequent use of iliac crest transplants by maxillofacial surgeons can be explained by the different training, since maxillofacial surgeons also learn and perform extraoral surgery while oral surgeons mainly learn intraoral procedures during their training. There is evidence in the literature that training and experience can have a significant influence on the therapy decision and its implementation [ 16 18 ]. Furthermore, it is remarkable that some surgeons, apparently due to their training, still practice methods such as iliac crest harvesting, although it has been shown that the resorption rate of these grafts is at best comparable but not lower than with alternative methods [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significantly more frequent use of iliac crest transplants by maxillofacial surgeons can be explained by the different training, since maxillofacial surgeons also learn and perform extraoral surgery while oral surgeons mainly learn intraoral procedures during their training. There is evidence in the literature that training and experience can have a significant influence on the therapy decision and its implementation [ 16 18 ]. Furthermore, it is remarkable that some surgeons, apparently due to their training, still practice methods such as iliac crest harvesting, although it has been shown that the resorption rate of these grafts is at best comparable but not lower than with alternative methods [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unmittelbar vor Beginn der Narkoseeinleitung sollte ein Team-Time-out stattfinden [12]. Im Zuge dessen müssen unter anderem die Reihenfolge und patientenadaptierte Dosierung der Medikamente sowie Strategien für potenzielle Komplikationen (z.…”
Section: Teamführungunclassified